Health Effects of Short‐Term Fluctuations in Macroeconomic Conditions: The Case of Hypertension for Older Americans. (November 2016) - Angrisani, Marco; Lee, Jinkook
Abstract: We investigate the health effects of short‐term macroeconomic fluctuations as described by changes in unemployment rate, house, and stock market price indexes. The 'Great Recession' provides the opportunity to conduct this analysis as it involved contemporaneous shocks to the labor, housing, and stock markets. Using panel data from the Health and Retirement Study over the period 2004–2010, we relate changes in hypertension status to changes in state‐level unemployment rate and house prices and to changes in stock market prices. We consider hypertension, a disease related to stress and of high prevalence among older adults, that has received little attention in the literature linking macroeconomic conditions to individual health. Our analysis exploits self‐reports of hypertension diagnosis as well as directly measured blood pressure readings. Using both measures, we find that the likelihood of developing hypertension is negatively related to changes in house prices. Also, decreasing house prices lower the probability of stopping hypertension medication treatment for individuals previously diagnosed with the condition. We do not observe significant associations between hypertension and either changes in unemployment rate or stock market prices. We document heterogeneity in the estimated health effects of the recession by gender, education, asset ownership, and work status. Copyright © 2016 John Wiley & Sons, Ltd.